Sequestration of 9-Hydroxystearic Acid in FAHFA (Fatty Acid Esters of Hydroxy Fatty Acids) as a Protective Mechanism for Colon Carcinoma Cells to Avoid Apoptotic Cell Death - Rodríguez, Juan Pablo (2019)
Fil: Rodríguez, Juan Pablo. Consejo Superior de Investigaciones Científicas. Instituto de Biología y Genética Molecular; Espana.